Valorization of Underutilized Mandarin Juice Byproduct Through Encapsulation of Flavonoids Using Freeze-Drying Technique - Marija Banožić; Adrijana Filipović; Jozo Ištuk; Mario Kovač; Anita Ivanković; Nikolina Kajić; Leona Puljić; Krunoslav Aladić; Stela Jokić (Applied Sciences, 2025)
This study evaluated Maltodextrin (MD), Gum Arabic (GA), and Carboxymethylcellulose (CMC) in different ratios as coating materials to encapsulate citrus pomace phenolic compounds. Citrus encapsulates were obtained by ultrasound-assisted extraction followed by the freeze-drying process and were characterized regarding the microencapsulation efficiency, physical, and chemical properties. Carrier material choice reflected a significant effect on encapsulation efficiency, phenolic compounds retention, and reconstitution properties of encapsulated extract. The encapsulation efficiency of prepared encapsulates ranked from 50.909% to 84.000%, and it was strongly dependent upon CMC addition. A wide range of reconstitution parameters (water absorption index-WAI and water solubility index-WSI) suggested possible release mechanism modifications. HPLC analysis revealed the presence of three main phenolic compounds, namely Hesperidin, Naringin, and Rutin. A wall material mixture of MD, GA, and CMC in the same proportions was optimal for freeze-drying. This combination resulted in encapsulates with a low moisture content (1.936 ± 0.012%) and a low water activity (0.110 ± 0.001), indicating prolonged stability. Based on the obtained results, freeze-drying as an encapsulation technique should be considered as a promising solution to recover compounds from industry byproducts and protect them from environmental and gastrointestinal circumstances.